Growing evolution of the electrification rate on heavy vehicles - Oliveira, Ricardo Manuel Fernandes Lemos de (2020)
In response to environmental impacts and all the limitations caused by fossil fuels, we have been witnessing in recent decades to the sharp development of hybrid electric and electric vehicles, particularly in heavy-duty passenger vehicles. Its proliferation is now widespread in virtually every major vehicle brand, reflecting operator confidence. In order to further mitigate the use of fossil fuels, the trend is to increase supply in 100% electric versions. However, the evolution of recent years, both in manufacturers commercial strategy of major brands and bodybuilders and in sales volume, seems to indicate a new demand stage for this kind of vehicles, which are still making the first steps in Portugal. However, high acquisition costs and limited autonomy are still major obstacles to a faster proliferation of electrification in heavy vehicles. Its strengths such as lower air and noise pollution, in addition to lower operating and maintenance costs, led to a growing acquisition in the Portuguese vehicle market, where 16 new heavy-duty passenger BEV have been sold this year. Real-world operational impacts of these vehicles indicate a energy use between 0.91 and 1.65 kWh/km depending on driving context. It has been also observed that operators are still adapting and not always using the full battery capacity.